2019
DOI: 10.1515/bot-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem-based management of seaweed harvesting

Abstract: Harvesting wild seaweeds has a long history and is still relevant today, even though aquaculture now supplies >96% of global seaweed production. Current wild harvests mostly target canopy-forming kelp, rockweed and red macroalgae that provide important ecosystem roles, including primary production, carbon storage, nutrient cycling, habitat provision, biodiversity and fisheries support. Harvest methods range from selective hand-cutting to bottom trawling. Resulting ecosystem impacts depend on extraction meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…While our sampling sites covered a broad geographical range, our results may not apply to all A. nodosum beds in eastern Canada especially those in regions with much lower growth rates. Lotze et al (2019) have reviewed the canopy and community impact of A. nodosum harvesting based on short-term studies and found that the type of harvest played a major role in mitigating the impacts. While a broad range of species has been found in A. nodosum beds (Seeley and Schlesinger 2012), little is known about the specific requirements of these species as to the A. nodosum beds.…”
Section: Harvest Impact-biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…While our sampling sites covered a broad geographical range, our results may not apply to all A. nodosum beds in eastern Canada especially those in regions with much lower growth rates. Lotze et al (2019) have reviewed the canopy and community impact of A. nodosum harvesting based on short-term studies and found that the type of harvest played a major role in mitigating the impacts. While a broad range of species has been found in A. nodosum beds (Seeley and Schlesinger 2012), little is known about the specific requirements of these species as to the A. nodosum beds.…”
Section: Harvest Impact-biomassmentioning
confidence: 99%
“…While cultivation accounts for most of the global production (96%; FAO 2018), harvesting of wild stocks continues to play a vital role in the sustainable livelihood of many coastal communities (Rebours et al 2014) despite the fact that only a fraction of the 10,000 algal species known are being commercially harvested (Mac Monagail et al 2017). Given the ecological importance of seaweed in primary production, carbon cycling, detrital production, and carbon sequestration as well as habitat and food for a whole community of organisms, a proper management framework is essential to ensure their sustainable harvest (Lotze et al 2019). Without considered management, some seaweed resources could become overexploited (Vásquez 2008), and their harvest can have an impact on multiple trophic levels within a food web (Lorentsen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…40 m (Dayton et al 1985;Harrold and Pearse 1987;Vásquez 1997;Graham et al 2007) coastline (Krumhansl et al 2016;. They form three-dimensional biogenic structures which offer habitat, shelter and food to a wide diversity of associated species, including species of commercial importance (Teagle et al 2017;Lotze et al 2019). As such, kelp species serve as foundation organisms that support high levels of biodiversity and provide a wide range of ecological goods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, kelp harvesting can cause changes in population dynamics and loss of standing biomass at regional scales (Geange 2014), affect predator-prey interactions (Lorentsen et al 2010), as well as impact kelp-associated species, including fish (O'Connor and Anderson 2010) and macroalgae (Vasquez and Santelices 1990). Impacts of harvesting at the population, community and ecosystem level can consequently impinge on the provision of ecological goods and services, with the magnitude of impacts dependent on harvesting methods, target species, and the scale, duration and frequency of harvesting (Waage-Nielsen et al 2003;Steen et al 2016;Lotze et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation